Calcium isotope fractionation during magmatic processes in the upper mantle. (15th March 2019) - Chen, Chunfei; Dai, Wei; Wang, Zaicong; Liu, Yongsheng; Li, Ming; Becker, Harry; Foley, Stephen F.
Abstract: The Earth's mantle has a complex history of partial melting and melt-peridotite reaction that have redistributed Ca and other elements between residues and melting products. Given the considerable Ca isotopic variation reported in mantle rocks, evaluation of the fractionation of stable Ca isotopes in magmatic processes in the mantle is critical to decode mantle evolution and the effect of recycled materials. We have performed precise and accurate Ca isotopic analyses on a series of well-characterized spinel-facies mantle peridotites (lherzolite, harzburgite and dunite, n = 29), pyroxenites (websterite, clinopyroxenite and orthopyroxenite, n = 15) and their mineral constituents (n = 8) from the Balmuccia and Baldissero peridotite massifs of the Ivrea Zone in the Italian Alps. These peridotites underwent variable degrees of melting and melt-peridotite reaction, whereas the pyroxenites are mainly the products of melt-peridotite reaction and crystallization of migrating basic melts from the asthenosphere. The lherzolites from Balmuccia and Baldissero show δ 44/40 Ca values of 0.94 ± 0.11‰ (2sd, n = 22), which are uniform within long-term external reproducibility (±0.14‰, 2sd). The δ 44/40 Ca values of the harzburgites (0.83‰ to 0.92‰) do not differ from those of lherzolites, including those with a history of intensive melt-peridotite reaction to form replacive dunites. The websterites and spinel clinopyroxenites display δ 44/40 Ca of 0.86 ± 0.10‰ (n = 14), within the range of the lherzolites and harzburgites. The indistinguishable δ 44/40 Ca among these very diverse mantle rocks is the consequence of the overwhelming control of stable Ca isotopes by clinopyroxene in the magmatic processes involved, because clinopyroxene dominates the budget of Ca (>90% for harzburgites; 93% to 99% for lherzolites, websterites and clinopyroxenites). Only the clinopyroxene-poor (<3 wt.%) dunites and orthopyroxenite show higher δ 44/40 Ca (e.g., 1.11‰ to 1.81‰ and 1.13‰, respectively). This reflects the signatures of olivine and orthopyroxene which display higher δ 44/40 Ca than clinopyroxene. These results and modeling suggest that negligible Ca isotope fractionation (<0.12‰) occurs during <25% of partial melting, silicate melt-peridotite reaction, or magmatic differentiation in the upper mantle. Only highly depleted harzburgite residues that formed by >25% melting and replacive dunites tend to display slightly heavier Ca isotopic compositions. Consequently, irrespective of their magmatic history, most fertile mantle rocks from different geological settings display a homogenous Ca isotope composition, summarized as, δ 44/40 Ca of 0.94 ± 0.10‰ (2sd, n = 47) for the Earth's mantle. The deviations in Ca isotopic variations observed in other mantle rocks may be attributed to kinetic isotope fractionation and metasomatism by melts with isotopic compositions influenced by recycled crustal materials.